Seabirds from the poles: microplastics pollution sentinels - Taurozzi, Davide; Scalici, Massimiliano (Frontiers in Marine Science, 2024)
The Arctic and Antarctica represent two of the most inhospitable and poorly investigated biomes in the world. Although polar regions are still perceived as some of the most pristine places still in existence, these remote places are no longer immune to anthropogenic pollution, in particular, micro- and nanoplastics. Seabirds, avian species feeding mainly at sea, are indicators of change in the environment and represent an early study group of ecological indicators for plastic pollution. The goal of this bibliometric overview is to evaluate international research trends on the impacts of microplastics (MPs) and nanoplastics (NPs) on seabirds inhabiting polar regions. A total of at least 13 seabird species were reported to have ingested MPs from 1983–2023. Overall, 1130 samples were investigated, including stomach content, pouch content, guano, and pellets. Pellets were the most investigated substrate (699), followed by stomach contents (309), guano (101), and pouch contents (21). A median of 31.5 MPs per sample was found in the Arctic, with an average of 7.2 MPs per sample. A median of 35 MPs per sample was found in Antarctica, with an average of 1.1 MPs per sample. Overall, MPs were most frequently found in fragment form. A total of 3526 MPs were retrieved from stomachs (3013), pellets (398), guano (75), and pouch contents (40). Polyethylene was the dominant plastic polymer found, followed by polypropylene and polystyrene. The monitoring of MP ingestion is crucial to mitigating the impacts on marine and terrestrial organisms. Standardized protocols could boost the safeguarding of seabirds and reduce the impacts of MPs on polar regions.